Eye tracking research on readers’ interactions with multimodal texts: a mini-review - Gatcho, Al Ryanne Gabonada; Manuel, Jeremiah Paul Giron; Sarasua, Rocky James Guevarra (Frontiers in Communication, 2024)
This mini-review advocates for the role of eye-tracking research in understanding readers’ engagement with multimodal texts. Synthesizing findings from a variety of studies, the review reveals how eye-tracking gives insights into sophisticated interactions between the textual, visual, and auditory elements within reading environments that assist both cognitive processing and comprehension. Several gaps were revealed: limited demographic scope, integration of advanced technologies, and substantial impact to the area of eye tracking and multimodal literacy. Future directions must therefore include studies across diverse populations, innovative technologies, and cross-discipline research studies. These directions are critical for advancing literacy development in an increasingly multimodal digital world.